HEMISPHERE DIFFERENCES IN AUDITORY STROOP TEST - Cohen, G; Martin, M (1975)
In an auditory Stroop test, right-handed subjects were required to judge the pitch of the following stimuli: two pure tones, one at a high frequency and one at a low frequency; two congruent words, "high," sung at the high frequency, and "low," sung at the low frequency; and two noncongruent words, "high" at low frequency and "low" at high frequency. A sequence of these stimuli was presented monaurally first to one ear, and then to the other. The Stroop effect (the difference between mean RT to congruent words, and mean RT to noncongruent words) was larger for right ear (left hemisphere) presentation. The same experiment was repeated dichotically with a competing message presented to the opposite ear. Again, the Stroop effect was larger for the right ear, and the ear differences were slightly more marked. The result is interpreted as reflecting hemispheric specialization for linguistic and nonlinguistic processing and a model of Stroop conflict in which response competition varies with the relative availability of the conflicting response. © 1975 Psychonomic Society, Inc.